2004
DOI: 10.3171/spi.2004.1.3.0311
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the nuclear factor—κB activation with pyrrolidine dithiocarbamate attenuating inflammation and oxidative stress after experimental spinal cord trauma in rats

Abstract: Object. The nuclear factor—κB (NF-κB) is a transcription factor that plays a pivotal role in the induction of genes involved in physiological processes and in the response to inflammation. The authors of recent studies have demonstrated that NF-κB and oxidative stress contribute to secondary injury after impact-induced spinal cord injury (SCI) in the rat. Dithiocarbamates are antioxidants that are potent inhibitors of NF-κB. The authors postulated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
51
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 72 publications
10
51
0
Order By: Relevance
“…To analyze the molecular mechanisms responsible for GILZ anti-inflammatory activity, we evaluated the classical NF-κB pathway [33,34] measured by Western blot IκB-α levels and nuclear translocation of NF-κB (NF-κB p65) twenty-four hours after SCI induction. A basal level of IκB-α was detected in the spinal cord from both WT and GILZ TG sham-operated animals (Fig.…”
Section: Gilz Over-expression Reduces Inos Nitrotyrosine and The Damentioning
confidence: 99%
“…To analyze the molecular mechanisms responsible for GILZ anti-inflammatory activity, we evaluated the classical NF-κB pathway [33,34] measured by Western blot IκB-α levels and nuclear translocation of NF-κB (NF-κB p65) twenty-four hours after SCI induction. A basal level of IκB-α was detected in the spinal cord from both WT and GILZ TG sham-operated animals (Fig.…”
Section: Gilz Over-expression Reduces Inos Nitrotyrosine and The Damentioning
confidence: 99%
“…Hamada et al [13] reported that intravenous injection of an iNOS inhibitor, N G -nitro-L-arginine methyl ester, reduces motor dysfunction in SCI models. La Rosa and colleagues [22] also reported that administration of pyrolidine dithiocarbamate (PDTC), which inhibits the activation of NF-jB and thus reduces iNOS expression, significantly improves motor function. These experimental results suggest that a NOS blocker and PDTC are candidate future pharmacologic treatments for SCI in humans.…”
Section: Limitations and Problems In The Present Studymentioning
confidence: 99%
“…It was reported that PDTC could protect against brain ischemia (Nurmi et al, 2004b) and spinal cord trauma (La Rosa et al, 2004). However, to date, no study has been conducted to investigate the influence of PDTC on cerebral vasospasm.…”
Section: Introductionmentioning
confidence: 99%